High resolution archaeology and neanderthal behavior time and space in level J of Abric Romaní (Capellades, Spain) - Carbonell i Roura, Eudald (Vertebrate Paleobiology and Paleoanthropology, 2012)
The aim of this book is to provide a new insight on Neanderthal behaviour using the data recovered in level J of Romaní rockshelter (north-eastern Spain). Due to the sedimentary dynamics that formed the Romaní deposit, the occupation layers are characterized by a high temporal resolution, which makes it easier to interprete the archaeological data in behavioural terms. In addition, the different analytical domains (geoarchaeology, lithic technology, zooarchaeology, taphonomy, anthracology, palaeontology) are addressed from a spatial perspective that is basic to understand human behaviour, but also to evaluate the behavioural inferences in the framework of the archaeological formation processes.